6(j-7)-13=43

Simple and best practice solution for 6(j-7)-13=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(j-7)-13=43 equation:


Simplifying
6(j + -7) + -13 = 43

Reorder the terms:
6(-7 + j) + -13 = 43
(-7 * 6 + j * 6) + -13 = 43
(-42 + 6j) + -13 = 43

Reorder the terms:
-42 + -13 + 6j = 43

Combine like terms: -42 + -13 = -55
-55 + 6j = 43

Solving
-55 + 6j = 43

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '55' to each side of the equation.
-55 + 55 + 6j = 43 + 55

Combine like terms: -55 + 55 = 0
0 + 6j = 43 + 55
6j = 43 + 55

Combine like terms: 43 + 55 = 98
6j = 98

Divide each side by '6'.
j = 16.33333333

Simplifying
j = 16.33333333

See similar equations:

| 2x+2(-1)=12 | | 4/7u=28 | | 2(-2)+2y=12 | | 200n=70 | | 204=-x+276 | | 3e^2x+1=9 | | 1.042=x(1-x) | | 9(2p+3)=81 | | 37=5m-63 | | 10c^2-33ct+20t^21= | | -7b-12=-4 | | 116=5v+16 | | (4x+5y)+(2x-11y)= | | 6a^2-15a-1=0 | | (5x-3)(x-2)(x+1)X=0 | | 6x+32=122 | | -11(26x-52)=44(-9x+3) | | 6p*3= | | 48/3=x/4 | | 5+3(-2)=-1 | | 30+0.35c=72 | | 3s=3 | | 2.5z=-75 | | 5(2)+3(0)=-1 | | -10t=-8t+10 | | 2.8=2n-5 | | W+3.34=5.64 | | 3x+(k+2)x=1-k | | -9+4d=9+2d | | 16-6(n)=2+n | | 4.8-1.8=0.4y | | -5*-25=25-10*-25 |

Equations solver categories